Верхнссалтовский и Нетайловский археологические памятники саптовской культуры - остатки древнего хазарского города - Крыганов, А.В. (Степи Европы в эпоху средневековья, 2001)
The Upper Saltov and Netailovka complexes are the largest archaeological sites of the Saltov culture. They are considered to be the remains of a handicraft and trading and important administrative centre in the north-west remote districts of Khazaria. Judging by archaeological reconnaissance, numerous pit and catacomb necropoles, still unknown, could be found around it. Though archaeological excavations have been carried out in the area for a long time, its complex investigation has not been undertaken as yet. The paper points out the most perspective directions for archaeological reconnaissance and excavations. We suppose that in the vicinity of the Pechenezhskoye storage reservoir most valuable archaeological sites could be found. Their investigation may bring new interesting data and discoveries. The hypothesis that three well-known names - Savgar, Sarada and Saltov - refer to one big Khazarian city could be verified by further research by both historians and philologists.